Pigmented perivascular epithelioid cell tumors of the orbit with NONO::TFE3 fusion: Molecular evaluation and literature review - Naoko Takeda-Miyata; Ken-ichi Yoshida; Miho Shirono; Akihide Watanabe; Yoji Kukita; Chie Sotozono; Eiichi Konishi (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To elucidate the clinical characteristics of rare orbital pigmented perivascular epithelioid cell tumors (PEComa) with transcription factor E3 (TFE3) rearrangement through a literature review. Observations: A 49-year-old female was referred to our hospital with a mass measuring 16 × 14 mm in the extraconal space of the right orbit. Suspecting hemangioma or distended hematoma clinically, the tumor was completely excised through the right nasal conjunctiva. Although initial histological evaluation raised the suspicion of malignant melanoma, subsequent immunohistochemistry and molecular analyses led to a diagnosis of TFE3-rearranged PEComa with the NONO::TFE3 fusion gene. The patient's visual function was preserved 14 months postoperatively, with no evidence of recurrence. Conclusions and importance: Although rare, TFE3-rearranged PEComa should be considered in the differential diagnosis of pigmented orbital tumors.